Philanthropy in Malaysian higher learning institutions - A. Rahman, Zakiah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Current economic crisis has brought many universities around the globe to source for the alternative funds to meet a substantial part of their expenditures (Haseeb, 2019). They are also confronting rising income inequality and declining rates of social mobility (Osilli, 2019). Malaysian public universities are not left behind. With more than 30 years of experience in international education and hosted more than 100 universities of both public and private (Malaysia Higher Education in Brief, n.d) it is high time for Malaysian universities to call for new approaches to meet with these complex challenges. Philanthropy has long history in universities and its contribution was immense. It supports the longevity of the university. In 1634, Harvard University started its first fund raising campaign and by some recent measures, Harvard receives an average of $3 million a day (Dogdson & Gann, 2018). Drawing from this argument and the recent trend of the university challenging environment, as well as the researcher own experience of more than 20 years in the education industry, this paper conceptually discussed on the current landscape of philanthropy in Malaysian Higher Learning Institutions (MHLI). This paper is derived, based on the available literature, with the hope to entail future academic research in philanthropy.